Preliminary Overview of the Economies of Latin America and the Caribbean 2019 - United Nations (United Nations, 2020)
This publication, one of the United Nations Economic Commission for Latin America and the Caribbean's most important annual reports, analyzes in its last edition the economic performance of the region throughout the year, including the international context and macroeconomic policies implemented by the Commission's Member States, while also providing an outlook for 2020